Comparative Analysis of Financial Performance before And during Covid-19 Pandemic - Astuti, Muthia; Simon, Zainal Zawir (SAN Scientific, 2023)
This study assesses the financial performance of technology sector firms listed on the IDX by utilizing various financial ratios, including Return on Assets, Total Assets Turnover, Current Ratio, Debt to Equity Ratio, and Sales Growth. The study employs a quantitative approach with multiple regression analysis, and the research relies on secondary data gathered from financial reports spanning from the third quarter of 2018 to the second quarter of 2021. The sample selection method employed purposive sampling, resulting in a sample size of nine companies. The normality of the data was assessed using the Kolmogorov-Smirnov method, revealing a non-normal distribution. As a result, the non-parametric Wilcoxon Signed Rank test was applied. The findings indicate significant disparities in the financial performance of technology sector companies listed on the IDX before and during the Covid-19 pandemic, particularly in metrics such as Total Assets Turnover, Current Ratio, Debt to Equity Ratio, and Sales Growth. However, the Return on Assets variable did not significantly differ before and during the Covid-19 pandemic. These insights can be valuable for stakeholders such as investors, creditors, and regulators in comprehending the associated risks and potential impacts when considering investment or extending credit to these entities